2017
DOI: 10.5194/acp-2017-1000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the optical properties of pure and transported anthropogenic dusts measured by ground-based Lidar

Abstract: In this study, the optical properties of pure dust (PDU) and transported anthropogenic dust (TDU) (also defined as polluted dust) are compared by using ground-based Lidar data for the period from October 2009 to June 2013. The total attenuated backscattering coefficient at 532 nm, the linear volume depolarization ratio and the color ratio are derived from the L2S-SM-II dual-band polarization Lidar. We found that the TDU has a spherical shape, a small linear volume depolarization ratio and a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This is the typical diurnal variation. Guo et al (2014) found a lack of diurnal variation, but a cycle of 4-7 days in the aerosol properties, indicating a reduced PBL diurnal trend during polluted periods. In figure 3 we didn't calculate the PBL, and in figure 5, it did not show the diurnal variation.…”
mentioning
confidence: 83%
“…This is the typical diurnal variation. Guo et al (2014) found a lack of diurnal variation, but a cycle of 4-7 days in the aerosol properties, indicating a reduced PBL diurnal trend during polluted periods. In figure 3 we didn't calculate the PBL, and in figure 5, it did not show the diurnal variation.…”
mentioning
confidence: 83%
“…Recent studies by Mahowald et al, 2010 andMulitza et al, 2010, found that the dust load, emission and deposition has increased over the 20 th century, concomitant with the development of agriculture. At the same time, analysis of dust sources [Ginoux et al, 2010], suggests that a significant fraction of transported dust has an anthropogenic origin Zhang et al, 2017] and along with mineral dust particles emitted from natural processes affect the Earth's albedo. Considerable research efforts have been devoted to quantify dust directive radiative forcing [Park and Jeong, 2008;Huang et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%